Revealing Islamic Cultural Values behind Capital Accounting Practices: A Study of Islamic Ethnomethodology - Thalib, Mohamad Anwar (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Purpose: This study aims to reveal the values of local wisdom behind the practice of capital accounting. Method: This study uses an Islamic paradigm with an Islamic ethnomethodology approach. Results: The results showed that the source of capital from the coachmen to buy the transportation of the hansom and horses were the gifts of their parents and other businesses. The capital is conditional on the value of responsibility to finance family needs and the value of patience for an undetermined amount of income. These two values reflect the parents' expressions in the form of delo sipati lo malu'o, tiloliyo kulu-kulu walaiyo modudu'o. It means to express feelings of family responsibility, and mopo'o tanggalo duhelo means full of patience. Implications: The results of this study seek to preserve accounting based on local culture. Novelty: The results of this study contribute to the presence of the concept of capital accounting practices based on Islamic cultural values in the Gorontalo community.